Pengaruh Kesejahteraan, Informasi, dan Kepercayaan terhadap Minat Berwakaf Uang dengan Akuntabilitas sebagai Moderasi di Kemenag Bantaeng: The Influence Of Welfare, Information, And Trust On Cash Waqf Interest With Accountability As A Moderating Variable At The Ministry Of Religious Affairs, Bantaeng Regency - Nurhidayat; Fathurrahman; Trisno Wardy Putra (Litera Academica Publishing, 2025)
This study aims to analyze the influence of welfare, information, and trust on the intention to donate cash waqf, with accountability as a moderating variable at the Religious Affairs Office of Bantaeng Regency. This research uses a quantitative approach with PLS-SEM analysis using SmartPLS 4.0, based on questionnaire data from 65 employees of the Religious Affairs Office of Bantaeng Regency. The results show that all independent variables significantly influence the intention to donate cash waqf. Accountability also significantly moderates these relationships and acts as a quasi-moderator. These findings confirm the importance of accountability in encouraging interest in cash waqf both directly and indirectly